PEMANFAATAN TONG SAMPAH ORGANIK MENGATASI SAMPAH DI CIBIRU ASRI CIBIRU WETAN BANDUNG - Susilawati, Elis; Hartini, Ni Nyoman Sri Mas; Supriadi, Dadih; Sutoro, Meylani; Priyadi, Akhmad; Lisni, Ida; Sya’bani, Oktaviani; Amanda, Ruli; Rahmanda, Erin; Wijaya, Youland Friccilia (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The community service activity titled "The Use of Organic Waste Bins to Address Waste in RT 03 RW 17, Cibiru Wetan Village, Cileunyi, Bandung" was carried out as an effort to tackle the issue of organic waste in the area. Poorly managed organic waste has the potential to pollute the environment and disrupt public health. This program aims to raise awareness, knowledge, and the ability of the community to manage organic waste into beneficial compost. The implementation stages include planning, providing facilities in the form of organic waste bins, education, compost-making training, and evaluation. A total of 2 units of organic waste bins have been distributed in strategic locations. The socialization successfully reached representatives of the residents, and the compost-making training involved 30 participants who showed positive results and were able to produce simple compost. The results of the activity indicate an increase in awareness and changes in community behavior regarding waste management. Residents have started to separate organic waste in their homes and utilize compost for small-scale agricultural activities. This program has also successfully reduced the volume of waste sent to landfills. The sustainability of the program requires the formation of community working groups to monitor implementation in the field, provide ongoing education, and collaborate with relevant parties. This program is expected to serve as a model for community-based waste management that can be replicated in other areas. With this activity, the community of Cibiru Wetan Village is expected to create a cleaner, healthier, and more environmentally friendly environment